Studi Deskriptif Pendidik Sebaya dalam Upaya Pendewasaan Usia Perkawinan di Kec. Pujon Kabupaten Malang - Shylvi Indah Triyani (Universitas Airlangga, 2016)
Currently the number of early marriages continued to increase from year to year. Adolescent are expected to play a role to overcome this issue. One of the eff orts made by the government is a adolescent educator program belong of BKKBN. Adolescent educators have a role as a communicator and leader to his adolescents. The purpose of this research was to identify the characteristics and history of adolescent educators in The Information and Counseling Center for adolescent in Pujon subdistrict at Malang regency. It was an observational study with a descriptive study design. This research used population sampling techniques. The variables studied respondent characteristics included gender, age, and education level. Adolescent educator long history of respondents adolescent educators, reason, recruiters, activities, evaluations, and the benefi ts. Study characteristics of adolescent educators were all female and all of them at the level of high school education. The most of them were 7 years old. Respondents history includes the largest adolescent educators had long time become for about 1 year. The most reason for being a adolescent educator because they want to prevent free sex and early marriage. People who did the most recruitment is the builder of the program. The most widely implemented were counseling activity. Most respondents never conduct routine evaluation. The benefi ts from this program for have more knowledge about health education. A lot of them want to have a routine training and learning as adolescent educator.